The global prevalence of sexual violence against pregnant women: a systematic review and meta-analysis. (2nd January 2022) - Shen, Xin; Dong, Hao; Jiang, Heng; Cao, Hui; Dowling, Rowan; Feng, Jing; Lei, Zihui; Zhao, Yuxin; Nui, Zhenyu; Pu, Bo; Lu, Z.; Gan, Yong
ABSTRACT: When committed against pregnant women, sexual violence may have adverse health consequences for both the mother and the unborn child. To date, no studies have systematically summarized the global prevalence of sexual violence against pregnant women. We conducted a comprehensive search of PubMed, Embase and Web of Science from inception dates to January 2021 for studies reporting the prevalence of sexual violence against pregnant women. Prevalence was estimated using a random-effects meta-analysis. Heterogeneity was evaluated using the I 2 statistic. Differences by study level characteristics were estimated through subgroup analysis and meta-regression. A total of 10 cross-sectional studies (a total of 8, 439 participants) were included. The pooled proportion of sexual violence was 0.31 (95% CI: 0.22–0.40). Subgroup analyses showed higher prevalence of sexual violence against pregnant women in the 2010–2019 period (0.35, 95% CI0.15–7.53) and developing countries (0.32, 95% CI0.19–0.45). Almost one in three (31%) pregnant women around the world has been a victim of sexual violence in their lifetime. Sexual violence against pregnant women continues to be a major public health challenge. The global prevalence of sexual violence against pregnant women warrants the collective attention of the entire society.